National Police of Ukraine as a Party to a Police Service Contract (Law and Safety, 2021)
Scientific approaches to determining the legal status of the employer in labor relations have been studied considered. The author has studied the norms of the Law of Ukraine “On the National Police”, which determine the identity of the employer and his authority to enter into a police service contract.It has been noted that the state is the employer in labor legal relations of police officers. However, employer powers in accordance with Part 1 of the Art. 63 of the Law of Ukraine “On the National Police” are delegated from the state to the National Police of Ukraine. Employer powers are directly exercised by the head of the police agency granting the right to accept and dismiss from the police. This person, on the one hand, is a representative of the employer, on the other hand – an employee.It has been stated that the Law of Ukraine “On the National Police”, defining the identity of the employer in the labor legal relations of police officers, did not enshrine the labor rights and responsibilities of the National Police of Ukraine as an employer. It is recommended to clearly define the list of labor rights and responsibilities of the National Police of Ukraine as an employer in the Law of Ukraine “On the National Police”. The following groups of labor rights of the National Police of Ukraine should be envisaged: 1) the right to select on the position of a police officer; 2) the right to accept, transfer and dismiss from the police; 3) the right to demand from the police officer to perform his / her functional duties; 4) the right to organize and manage the service; 5) the right to apply incentives; 6) the right to compensation ин police officers for the damage caused to the property of the police agency as a result of the violation of their functional duties by police officers. It is also necessary to consolidate the following groups of labor responsibilities of the National Police of Ukraine: 1) ещ provide the police щаашсук with work that meets the job descriptions and functional responsibilities of the relevant position; 2) ещ create appropriate service conditions necessary for the performance of functional duties; 3) to ensure proper rest of police officerі; 4) to provide timely financial support to police officerі and in the full extent; 5) to provide social protection for police officers; 6) to ensure the protection of the life and health of police officers, the life and health of family members, as well as their property.
Keywords: police; a police officer; a contract; labor legal relations; an employer; an employee.